Programmed frozen embryo transfer cycles are associated with a higher risk of abnormal placental development: a retrospective cohort study of singleton live births - Wang, Fuxin; Wang, Qi; Song, Ye; Ding, Jie; Li, Hong; Meng, Qingxia (Frontiers in Endocrinology, 2023)
Introduction: Abnormal placental development can lead to adverse outcomes for both mother and fetus. The effect of different types of endometrium preparation regimens of frozen-thawed cycles on the placental development features associated with the perinatal outcomes remains unclear. we conducted a retrospective cohort study to assess the impact of specific endometrial preparation regimens on placenta-mediated pregnancy complications in singleton live births. Methods: A retrospective cohort study was conducted evaluating data of all singleton live births both conceived naturally or by IVF therapy from 2018 to 2020 at our hospital. Two exposed groups of frozen-thawed embryo transfer were created by the endometrium preparation regimen as the natural cycles and the hormone replacement cycles. The nonexposed group was the singleton pregnancies conceived naturally. The obstetrical and perinatal outcomes were compared among the three groups using multivariate analysis to adjust the results for determinants potentially associated with the abnormal placental development. Results: A total of 2186 pregnant women with singleton live births were included in our final analysis and were allocated to the group of pregnancies resulting from naturally conceived (n=1334), NC-FETs(n=217) and HRT-FETs(n=635). After adjusting for maternal age and parity, no significant difference was observed in the risk of placental disorders between NC-FET cycles and natural conceived pregnancies (aOR 1.16; 95%CI 1.31-7.01), while HRT-FET cycles were associated with a higher occurrence of placental disorders (aOR 5.36; 95%CI 3.63-8.05). Using the NC-FET group as a reference and adjusting for confounders such as maternal age, parity, endometrial thickness, and number of embryos transferred, we found that abnormal placentation in HRT-FET cycles mainly manifested as abnormal placental attachment, including placental adhesion and placenta increta (aOR 2.50, 95%CI 1.36-4.90). The dysfunction of placentation in HRT-FET cycles was independently associated with the type of infertility, the total dose of Femostone and thinner endometrium. Additionally, placental disorders in the HRT-FET group were associated with higher rate of preeclampsia, postpartum hemorrhage and Cesarean section. Conclusion: Our retrospective study revealed that the HRT-FET has a substantial impact on placental development, resulting in a higher incidence of preeclampsia, postpartum hemorrhage and Cesarean section. These findings have significant implications for clinical decision-making.